Mechanics of microelectromechanical systems - Lobontiu, Nicolae; Garcia, E. (Ephrahim) (New York : Kluwer Academic, 2005)
"This book offers a comprehensive coverage to the mechanics of microelectromechanical systems (MEMS), which are analyzed from a mechanical engineer's viewpoint as devices that transform an input form of energy into output mechanical motion (in the case of actuation) or that can operate with the reversed functionality (as in sensors) and convert an external stimulus, such as mechanical motion, into (generally) electric energy."--Jacket.
Stiffness Basics.- Microcantilevers, Microhinges, Microbridges.- Microsuspensions.- Microtransduction: Actuation and Sensing.- Static Response of Mems.- Microfabrication, Materials, Precision and Scaling.
Includes bibliographical references and index.
Keywords: Microelectromechanical systems